Spontaneous writing: co-creating a play - Balaska, Ioulia (Murmurations: Journal of Transformative Systemic Practice, 2022)
In this paper, I propose a way of systemic work through art and specifically through theatrical practice in order to prompt this kind of creative writing called spontaneous writing. In the Improvisational Experiential Theatre method that I practise, spontaneous writing is prompted by theatrical improvisations. The writings of the group members compose a play, which is brought before a theatre audience. Systemic practitioners often use writing in their work with people in order to help them to express themselves. Spontaneous writing which aims for the creation of a theatrical play triggers the group members to release their deeper thoughts, their feelings and their body, and to express themselves mostly poetically. It creates the space that helps them to connect with society, writing about social issues that touch everyone. And when these persons, who are not actors, present their own play on a stage, they see themselves as protagonists in their lives and at the same time as active members of society. I hope that this paper will motivate systemic practitioners to use the art, in any form, in their work with people. Περίληψη (Greek) Σε αυτό το άρθρο, προτείνω ένα τρόπο συστημικής δουλειάς μέσω της Τέχνης και συγκεκριμένα μέσω της θεατρικής πράξης, προκειμένου να προκληθεί το είδος της δημιουργικής γραφής που ονομάζεται αυθόρμητη γραφή. Στην μέθοδο Αυτοσχεδιαστικού Βιωματικού Θεάτρου που εφαρμόζω, η αυθόρμητη γραφή κινητοποιείται από θεατρικούς αυτοσχεδιασμούς. Τα κείμενα των μελών της ομάδας συνθέτουν ένα θεατρικό έργο, που το παρουσιάζουν στο κοινό.